The quality of care received by HIV patients without a primary provider. - Ding, L; Landon, B E; Wilson, I B; Hirschhorn, L R; Marsden, P V; Cleary, P D (AIDS care, 2008)
The goal of this study was to compare the quality of care received by HIV patients who report that their primary HIV care provider is a physician, a nurse practitioner (NP) or a physician assistant (PA) to that of patients who cannot identify a primary HIV provider. We used data from patients who participated in the HIV Cost and Services Utilization Study (HCSUS), a study of a probability sample of non-institutionalized HIV-infected individuals in care in the US. We compared patients who did and did not name a primary HIV care provider in terms of patient and care site characteristics, and level of clinician HIV expertise. Care quality measures included receipt of highly active antiretroviral therapy (HAART), reported problems with care, satisfaction with care, unmet needs and perceived access to care. Patients in care who did not report having a primary HIV care provider received HAART at significantly lower rates (p<0.05) and were less satisfied with their care (p<0.05) than patients with a primary HIV care provider, after adjusting for illness severity and other patient characteristics. There were similar but non-significant trends for reported problems, unmet needs and perceived access to care. Patients who had lower income or were drug users were more likely not to have a primary provider. We conclude that having a primary HIV care provider who is knowledgeable about a patient's care is related to the quality of medical care received by persons with HIV infection.
Keywords: Adolescent; Adult; Antiretroviral Therapy, Highly Active; Clinical Competence; Female; Health Services Accessibility; HIV Infections; Humans; Male; Middle Aged; Patient Satisfaction; Primary Health Care; Quality of Health Care; Questionnaires; United States